(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
productive seasons on Prolactin hormone , milk composition and metabolites in the blood of local cows. The study included 24 dairy cows during the second, third and fourth milk seasons . The results showed that the milk season was a significant effect (p<0.05) on the concentration of the prolactin hormone, fat , lactose and non- fat solids (SNF) of milk . There was non significant effect of the milk season in metabolic concentrations (glucose, total cholesterol and total protein). The results of the study showed a positive correlation between prolactin hormone, lactose and SNF and a significant positive correlation (p<0.01) between prolactin hormone and fat and SNF of milk and high correlation (p<0.01) between the milk season and prolactin and significant correlation (p<0.05) between prolactin hormone and total cholesterol. We conclude from this study that the milk season has an effect on milk hormone and a link between milk hormone, milk components and metabolic substances in the blood.